Introducing ROTAVAC® to the occupied Palestinian Territories: Impact on diarrhea incidence, rotavirus prevalence and genotype composition. Issue 4 (23rd January 2023) - Rennert, Wolfgang; Hindiyeh, Musa; Allahham, Majd; Mercer, Laina D.; Hamad, Khalil I.; Ghuneim, Nedal I.; A. M. Eljaro, Zuheir; Abu-Awwad, Fakhr; Bozya, Yaser; Hjaija, Diaa; Bhat, Niranjan; Leader, Troy; et al.
Abstract: Background: Rotavirus infection remains an important cause of morbidity and mortality in children. The introduction of vaccination programs in more than 100 countries has contributed to a decrease in hospitalizations and mortality. This study investigates the epidemiological impact of the rotavirus vaccine ROTAVAC® in the Palestinian Territories, the first country to switch from ROTARIX® to this new vaccine. Methods: Clinical surveillance data was collected from children younger than 5 attending outpatient clinics throughout Gaza with diarrhea between 2015 and 2020. The incidence of all-cause diarrhea was assessed using an interrupted time-series approach. Rotavirus prevalence was determined at the Caritas Baby Hospital in the West Bank using ELISA on stool specimen of children younger than 5 with diarrhea. Genotyping was performed on 325 randomly selected rotavirus-positive samples from January 2015 through December 2020 using multiplex PCR analysis. Results: Average monthly diarrhea cases dropped by 16.7% annually from introduction of rotavirus vaccination in May 2016 to the beginning of the SARS-CoV-2 epidemic in March 2020 for a total of 53%. Case count declines were maintained after the switch to ROTAVAC® in October 2018. Rotavirus positivity in stool samples declined by 67.1% over the same period without change following the switch to ROTAVAC®. The distribution of predominant genotypes in rotavirus-positive stool samples changed from a pre-vaccination G1P [8] to G9P[8] and G12P[8] during the ROTARIX® period and G2P[4] after the introduction of ROTAVAC®. Conclusion: ROTAVAC® has shown epidemiological impact on par with ROTARIX® after its introduction to the national immunization schedule in the Palestinian Territories. A molecular genotype shift from a pre-vaccination predominance of G1P[8] to a current predominance of G2P[4] requires more long-term surveillance.